ASSESSMENT OF CURRENT TRANSFORMER USING HEALTHY INDEX AT ULTG PANAKKUKAN - Rizqan, Uais; Thaha, Sarma (Jurnal Teknologi Elekterika, 2025)
Current transformers (CTs) play a crucial role in the measurement and protection of electrical networks, directly impacting the performance and stability of the distribution system. Over time, the condition of current transformers can degrade due to factors like age, environmental conditions, and overloads. To ensure the health status of these transformers, an assessment method using the Healthy Index (HI) is applied. This research utilizes data from tests on tan delta, insulation resistance, ratio, thermography, excitation, and the age of the current transformer. The data is categorized into two factors: the Conditional Assessment Factor (CAF), which provides a real-time condition overview from tan delta data (where values above 1% indicate poor and values below or equal to 1% indicate good condition), insulation resistance (where values below or equal to 1 Mega Ohm/1kV indicate poor and above 1 Mega Ohm/1kV indicate good), thermography (where temperatures above 4°C are considered poor, temperatures between 1°C and 3°C are medium, and normal temperatures relative to ambient conditions are good), and ratio; and the Performance Assessment Factor (PAF), which assesses equipment performance based on transformer age. Age classifications are 20-35 years as poor, 16-20 years as medium, and below 16 years as good. Following the gathering of CAF and PAF data, a systematic calculation of each factor's weighting is conducted using the Assessment Healthy Index (AHI) Calculation method, resulting in assessment ratings of 1 for poor, 6 for medium, and 9 for good. From these categories, conclusions can be drawn regarding the next steps for the current transformer, determining whether repair or replacement with a new transformer is necessary.